Agent liquidity: A catalyst for mobile money banking among the unbanked poor population in rural sub-Saharan Africa - George Okello Candiya Bongomin; Charles Akol Malinga; Alain Amani Manzi; Rebecca Balinda (Cogent Economics & Finance, 2023)
AbstractA large body of research shows that mobile money through its agent networks can potentially increase financial inclusion, especially in the unbanked rural regions of the developing world. This study intends to establish whether agent liquidity has a significant moderating effect in the relationship between mobile money services and financial inclusion of the unbanked poor population in rural sub-Saharan Africa. The data were collected from mobile money users through a cross-sectional approach using a semi-structured quantitative questionnaire and Analysis of Moment Structures was used to test for the moderating effect of agent liquidity between mobile money services and financial inclusion. The results revealed a significant moderating effect of agent liquidity in the relationship between mobile money services and financial inclusion of the unbanked poor population in rural sub-Saharan Africa with data collected from rural Uganda. Agent liquidity enhances access to and usage of mobile money services by 27 percentage points to spur financial inclusion among the unbanked rural poor population. Similarly, agent liquidity has a direct significant effect on access to and usage of mobile money services among the unbanked rural poor population. Overall, the results showed that agent liquidity plays a significant and positive moderating role between mobile money services and financial inclusion. The findings from this study can help mobile money providers to increase the amounts of float to boost agent liquidity to meet instant cash-in and cash-out demands of customers. Besides, regulations on mobile money agents should be loosen to allow more village “dukas” (small village shops) to offer mobile money financial services to crowd-in more unbanked rural poor population into the digital financial system.